Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise. Issue 6 (6th June 2019) - Quinzin, Maud C.; Sandoval‐Castillo, Jonathan; Miller, Joshua M.; Beheregaray, Luciano B.; Russello, Michael A.; Hunter, Elizabeth A.; Gibbs, James P.; Tapia, Washington; Villalva, Freddy; Caccone, Adalgisa
Abstract: Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises (Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger, and an extant species, C. becki, which were recently found in the endemic range of C. becki, from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation. Abstract : Reproducción en Cautiverio Informada Genéticamente de Híbridos de una Especie Extinta de Tortuga de las Galápagos Resumen: La hibridación representa un obstáculo importante para la conservación de especies ya que amenaza tanto a la integridad genética como al potencial adaptativo. Aun así, la hibridación ocasionalmente puede ofrecer una oportunidad sin precedentes para la recuperación de una especie si el genoma de un taxón extinto está presente entre los híbridos vivientes de tal manera que la reproducción selectiva pudiera recuperarlo. Exploramos los elementos de diseño para el establecimiento de un programa de reproducción en cautiverio de la tortuga de las Galápagos ( Chelonoidis spp.) construido en torno a los individuos con linajes mixtos que incluyeran una especie extinta. Los individuos fueron los híbridos de la especie extinta en la Isla Floreana, C. niger, y la especie viviente C. becki, encontrados recientemente en la distribución geográfica endémica de la segunda especie en el Volcán Wolf (Isla Isabela). Combinamos los datos genotípicos de 35 tortugas con un linaje cargado de C. niger usando simulaciones futuras de la descendencia generada por el programa para explorar las estrategias de reproducción en cautiverio que maximizaran en general la diversidad genética y el linaje de C. niger a la vez que se ajustaba a las restricciones de recursos, la biología de la especie y la urgencia por regresar las tortugas a la Isla Floreana para facilitar la restauración del ecosistema. En general, la diversidad genética se maximizó cuando en la simulación las tortugas estuvieron organizadas en grupos de reproducción relativamente pequeños y cuando cantidades sustanciales del genoma de C. niger fueron capturados con base en los recursos disponibles para reproducir selectivamente a las tortugas en cautiverio. La diversidad genética se vio especialmente maximizada cuando las crías reproducidas en cautiverio fueron liberadas en lugar de ser utilizadas como reproductoras adicionales. Nuestros resultados proporcionan una guía práctica y basada en la genética para la inclusión de híbridos con representación genómica de un taxón extinto en los programas de restauración de especies. Cuando incorporamos a los híbridos con diversidad genética que previamente se creía perdida en los programas con el propósito de la reintroducción de especies, nuestro estudio informa al debate continuo sobre el valor de los híbridos para la conservación de la biodiversidad. 摘要: 杂交对物种保护提出了重大挑战, 因为它威胁着物种的遗传完整性和适应性潜力。然而, 如果一个已灭绝类群的基因组存在于现存的杂交种中, 那么杂交也可以为物种恢复提供前所未有的机遇, 通过选择性育种重新获得灭绝物种的基因组。本研究探讨了如何利用含有已灭绝物种基因组的混合血统个体, 为加拉帕戈斯陆龟 （Chelonoidis spp .） 建立圈养繁殖计划。我们的目标个体是弗洛里安娜岛灭绝物种 C. niger 与近期在其分布范围内伊莎贝拉岛沃尔夫火山发现的现存物种 C. becki 的杂交后代。我们将 35 只含有较高比例 C. niger 血统的乌龟的基因型数据与对该计划获得后代的前进式模拟相结合, 在满足总体遗传多样性和 C. niger 血统最大化, 且考虑资源限制、物种生物学特性和弗洛里安娜岛急需重引入乌龟来促进生态系统恢复的情况下, 分析了可能的圈养繁殖策略。在模拟实验中, 建立相对较小的乌龟繁殖群时的总体遗传多样性最高, 且根据已有资源对圈养乌龟进行选择性育种可以捕获大量的 C. niger 基因组。若将圈养繁殖的后代释放到野外而不是继续用于繁殖, 则遗传多样性会特别高。我们的研究结果为将携带已灭绝类群的代表性基因组的杂交种纳入物种恢复计划提供了基于遗传学的实践指导。我们的研究还表明, 可以在物种重引入项目中纳入携带了被认为已经丢失的遗传多样性的杂交种, 这也为目前杂交种在生物多样性保护中的价值的争论提供了信息。【翻译: 胡怡思; 审校: 聂永刚】 Abstract : Article impact statement : Hybrid individuals provide invaluable genomic resources for captive breeding and restoration of an extinct Galapagos giant tortoise.